Protection on the territory and customary rights of Cibarani Wewengkon in Lebak Regency, Banten, Indonesia - Satria Iman Prasetyo; Eko Priyo Purnomo; Rohana Ahmad; Aqil Teguh Fathani; Delila Putri Sadayi (Universitas Negeri Malang, 2023)
This study examines the influencing factors of policies related to customary rights or Wewengkon implementation in the Cibarani indigenous peoples, affecting the destruction of Leuweng Titipan Mount Liman. The protection and supervision of the Cibarani Wewengkon are regulated by the Lebak Regional Government Number 8 of 2015 concerning the Recognition, Protection, and Empowerment of the Kasepuhan Customary Law Community. However, despite getting supervision and protection, natural damage caused by unlicensed gold miners continues to wreak natural harm. As a result, two hectares of forest on Mount Liman were deforested. This research used a qualitative research approach and collected data through a literature study. The results indicated that the influencing factors of inadequate protection for the Cibarani Wewengkon are the ignorance of the Lebak Regional Government regarding the supervision and protection of the Cibarani Wewengkon. Their insensibility is induced by the issues in transmission of information or poor communication between policymakers, such as the Lebak Regency house of representative and the regent, resulting in vague details on the authority to safeguard and supervise.